A new species of the genus Calchaenesthes Kraatz, 1863 (Coleoptera, Cerambycidae) from Cyprus - Lazarev, Maxim (Zootaxa, 2023)
The new species is similar to Calchaenesthes primis Özdikmen, 2013 (Figs. 3-4) described from south Anatolia (Içel province) and was often mixed with it (Ambrus, Grosser & Hrbek, 2014; Özdikmen & Cihan, 2018; Danilevsky, 2020). Recently I received a good series of Calchaenesthes from Cyprus, and see several important characters, which distinguish the island population. It is described below as a new species.